Demographics of plateletpheresis donors and session profile in a teaching institute of Punjab - Harnoor Singh Bhardwaj; Amarjit Kaur; Rajesh Kumar; Sonia Gupta (Asian Journal of Transfusion Science)
BACKGROUND: Over decades, increased demand of platelet transfusions for patients with various conditions led to accelerated use of technologically advanced plateletpheresis. AIMS: Study the demographics of plateletpheresis donor and plateletpheresis session profile. SETTING AND DESIGN: Prospective, cross-sectional, open label study. MATERIALS AND METHODS: Plateletpheresis performed on Trima Accel (TA) and mechanical circulatory support (MCS) + during 2017–2018 on donors selected according to the guidelines. STATISTICAL ANALYSIS: SPSS (version 17) for windows statistical package. RESULTS: Two thousand eighty hundred and thirty-six plateletpheresis procedures were done, out of which 666 (23.48%) were done on TA while 2170 (76.51%) were done on MCS +. Maximum donors, 1437 (55.66%) were in the 21–30 years category; Mean age was 30.75 years ± 8.44 standard deviation (SD); range18–65 years. Maximum donors 1185 (41.78%) were in the 61–70 kg category with mean weight - 74.33 kg ± 9.80 SD and mean height - 170.46 cm ± 4.99 SD only 4 (0.15%) donors were females. Two thousand six (70.73%) donors were voluntary, with 1620 (57.12%) repeat donors. Mean platelet count was 272.98 ± 56.59 × 109/L with maximum donors having platelet count between 200 and 300 × 109/L and ranged from 157 to 508 × 109/L. Mean hemoglobin of donors - 14.87 g % ± 3.16 SD; total serum protein - 6.31 g/dl ± 4.8 SD. Mean platelet yield was 3.50 × 1011 ± 0.71 SD; ranged from 2.9 to 7 × 1011. Plateletpheresis session profile of reactors and nonreactors showed that acid citrate dextrose used in reactors was more - 353.44 ml as compared to nonreactors - 311.72 ml. Reactors showed more volume of whole blood processed - 2899.43 ml as compared to nonreactors - 2601.63 ml. Time taken for completing the session was more in reactors - 82.40 mins as compared to nonreactors - 70.80 min. Platelet yield was 3.79 × 1011 and 3.49 × 1011 and plasma volume was 275.6 ml and 261.2 ml in reactors and nonreactors respectively. CONCLUSION: Demographics of plateletpheresis donors and session profile are vital for their safety.